2019
DOI: 10.15376/biores.14.3.6544-6557
|View full text |Cite
|
Sign up to set email alerts
|

Bio-deinking of mixed office waste paper by Penicillium citrinum NCIM-1398 and its comparative study with conventional chemical deinking

Abstract: Penicillium citrinum NCIM-1398 is a co-producer of endo β-1,4-glucanase, xylanase, and amylase enzymes. The synergistic effect of the enzymes present in the cocktail was found to be advantageous in deinking white mixed office waste (MOW) paper. Enzymatic deinking of MOW reduced the dependence on chemicals by up to 50% during chemical deinking and improved optical properties compared with the chemical deinking process. The chemi-enzymatic approach improved pulp brightness by 12.6% compared with MOW pulp. The ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, toxic byproducts are produced during the chemical process (Kumar et al 2018a), which results in environmental pollution. In comparison, a biobleaching process is a less intrusive, less expensive method (An et al 2002;Biswas et al 2019b) and it has been shown to be an eco-friendly technology compared to chemical processes (Biswas et al 2019a;Kumar et al 2019b). Therefore, microbial degradation of dyes is gaining popularity in the paper and textile industries.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, toxic byproducts are produced during the chemical process (Kumar et al 2018a), which results in environmental pollution. In comparison, a biobleaching process is a less intrusive, less expensive method (An et al 2002;Biswas et al 2019b) and it has been shown to be an eco-friendly technology compared to chemical processes (Biswas et al 2019a;Kumar et al 2019b). Therefore, microbial degradation of dyes is gaining popularity in the paper and textile industries.…”
Section: Introductionmentioning
confidence: 99%